2019
DOI: 10.1017/s0033291719002940
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and depressive phenotypes: evidence from medical records from over 12 000 patients and brain morphology

Abstract: BackgroundPreclinical and human studies suggest an association between chronic inflammation and the development of depressive behaviors. This is proposed to occur through downstream effects of inflammatory cytokines on neuroplasticity, neurogenesis and neurotransmitter function, although the neural correlates remain poorly understood in humans.MethodsIn Study 1, structural magnetic resonance imaging and serum inflammatory cytokine data were analyzed from 53 psychiatrically healthy female participants. Correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 56 publications
1
18
1
Order By: Relevance
“…In recent years, many studies have shown that the pathogenesis and progression of depression are related to the overreaction of inflammation and immune responses [4,44]. The inflammasome is an inducer of immune response with the function of identifying and targeting multiple pathogens [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many studies have shown that the pathogenesis and progression of depression are related to the overreaction of inflammation and immune responses [4,44]. The inflammasome is an inducer of immune response with the function of identifying and targeting multiple pathogens [45].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence revealed a close link between inflammation and major depression disorder [2,3]. The nod-like receptor pyrin-containing pyrin domain 3 (NLRP3) inflammasome is one of the most widely studied inflammasomes [4]. After NLRP3 inflammasome is assembled and activated, it activates caspase-1 by proteolytic cleavage, which in turn, converts pro-IL-1β into bioactive IL-1β, leading to inflammatory responses in bodies [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have shown that the pathogenesis and progression of depression are related to the overreaction of inflammation and immune responses [4,39]. The inflammasome is an inducer of immune response with the function of identifying and targeting multiple pathogens [40].…”
Section: Discussionmentioning
confidence: 99%
“…Depression is considered to be relevant with the activation of chronic, low‐grade inflammatory responses and cell‐mediated immunity 130,131 . Chronic inflammatory reactions cause neurons apoptosis in brain regions associated with emotion regulation such as hippocampus, 132,133 leading to impairment of synaptic plasticity. Ketamine could normalize abnormal neurobehaviours induced by neuroinflammation through regulating the interleukin (IL)‐1β, tumour necrosis factor (TNF)‐α and IL‐6 134 .…”
Section: Synaptic Plasticitymentioning
confidence: 99%